2009
DOI: 10.1002/art.24642
|View full text |Cite
|
Sign up to set email alerts
|

HLA–B51/B5 and the risk of Behçet's disease: A systematic review and meta‐analysis of case–control genetic association studies

Abstract: Objective To quantify by meta-analysis the genetic effect of the HLA–B5 or HLA–B51 (HLA–B51/B5) allele on the risk of developing Behçet’s disease (BD) and to look for potential effect modifiers. Methods Relevant studies were identified using the PubMed Medline database and manual searches of the literature. Pooled odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated by using the random-effects model. Subgroup meta-analyses and meta-regression analyses were undertaken to investigate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
239
1
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(257 citation statements)
references
References 77 publications
(119 reference statements)
8
239
1
9
Order By: Relevance
“…This finding is consistent with earlier studies on HLA-B5/B51 positivity. (de Menthon et al, 2009;Maldini et al, 2012).…”
Section: Hla-b51 Subtypes In Behçet's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with earlier studies on HLA-B5/B51 positivity. (de Menthon et al, 2009;Maldini et al, 2012).…”
Section: Hla-b51 Subtypes In Behçet's Diseasementioning
confidence: 99%
“…Although the pathogenesis is not exactly known, it is believed to be triggered by microbial or environmental factors, with a genetic predisposition. In many ethnic groups that settled along the ancient Silk Road, a significant relationship is detected between BD and HLA-B51positivity (Kaya et al, 2002;Kötter et al, 2004;de Menthon et al, 2009;Song and Kang, 2012;Hughes et al, 2013;Houman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although many cases of BS are sporadic, familial aggregation is observed with varing frequencies in different populations (more frequenct in juvenile patients) (42,43). The strongest genetic factor associated with the risk of Behçet syndrome is the HLA-B5/B51 allele carrier state, which is observed more frequently in familial cases compared with sporadic BS (44,45). In a meta-analysis that comprised 4 800 patients with BS and 16 289 controls, the HLA-B51/B5 frequency was found as 57.2% in patients with BS, and 18.1% in the controls (OR 5.78, 95% CI: [5.00-6.67]) (45).…”
Section: Known Susceptibility Genes In Commonly Observed Diseases Witmentioning
confidence: 99%
“…The strongest genetic factor associated with the risk of Behçet syndrome is the HLA-B5/B51 allele carrier state, which is observed more frequently in familial cases compared with sporadic BS (44,45). In a meta-analysis that comprised 4 800 patients with BS and 16 289 controls, the HLA-B51/B5 frequency was found as 57.2% in patients with BS, and 18.1% in the controls (OR 5.78, 95% CI: [5.00-6.67]) (45). In another study, it was shown that the HLA-B*5101 variant had a strong relation with BS, and the MICA-A6 allele was reported to increase predisposition to BS (46 …”
Section: Known Susceptibility Genes In Commonly Observed Diseases Witmentioning
confidence: 99%
“…A number of previous studies have indicated that BD is associated with environmental risk factors such as infectious agents, which are likely involved in the susceptibility to the disease (3). The HLA-B51 allele polymorphism has been associated with the pathogenesis of BD (4). Furthermore, major histocompatibility complex (MHC) class I chain related A (MICA) is a functional gene located between the HLA-B and tumor necrosis factor genes on the short arm of human chromosome (5).…”
Section: Introductionmentioning
confidence: 99%